Road traffic collision: Reasons and the future - Azizi Yahaya; Balan Rathakrishnan; Suraya Fadilah Ramli; Ismail Maakip; Peter Voo Su Kiong; Abu Bakar Madin (Hong Kong Journal of Social Sciences, 2022)
This paper focuses on identifying the determinants of Road Traffic Collision (RTC) and forecasting the number of RTC in Malaysia for the next ten years. The correlation test employed 15 years’ data on RTC, population, gross domestic product (GDP), new drivers, and registered vehicles that were collected from JKJR and World Bank Group. SPSS software enabled to determine through Pearson’s product-moment correlation whether population, registered vehicles, GDP, or new drivers were RTC determinants in Malaysia. The overall results showed that registered vehicles, population and gross domestic product (GDP) were the main determinants of RTC; motorcycle accidents attained the highest rank of injured RTC, while bus accidents were ranked as the lowest RTC causing injuries and death. The number of RTA fatalities was observed to decrease by 0.82% each year for the following ten years, with 5588 expected RTA fatalities in 2029. The government was alarmed, and concerns arose due to the apparent fact that RTC is increasing fast. In 2018, 6,284 people were killed in RTCs. Henceforth, a reduction in the number of RTCs is urgently required. This study recognized the pattern of road accidents in Malaysia and gave some measurements to avoid severe accidents. The intervention of method was proposed to ensure the the reduction of road accident percentage. The results help the government reduce the number of such fatality cases and take the necessary actions for mitigation plans.